2019
DOI: 10.20517/2394-5079.2019.013
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year survival and recurrence of hepatocellular cancer

Abstract: Aim: Long-term survival after hepatocellular cancer (HCC) is difficult to achieve likely related to recurrence. This study aimed to identify factors that were predictive of 10-year survival after the diagnosis of HCC. Methods:In a prospectively collected database of 1374 HCC cases , we identified 70 patients who survived over 10 years regardless of treatment. We then identified 164 patients in the entire cohort who either had liver resection or transplant, and died before 10 years. Demographics, tumor characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…The long-term prognosis of patients with recurrent HCC remains poor because of deterioration of liver function with repeated recurrences even after curative treatment following early detection of HCC and during a successful regular surveillance program ( 5 ). Therefore, in the treatment of HCC, recurrence after curative treatment is an important indicator that is negatively related to long-term survival ( 6 ). To improve recurrence-free survival (RFS) in patients with HCC, several studies on adjuvant therapy have been conducted; however, none of these studies provide sufficient evidence of improvement except for antiviral treatment for HBV- or HCV-related HCC ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The long-term prognosis of patients with recurrent HCC remains poor because of deterioration of liver function with repeated recurrences even after curative treatment following early detection of HCC and during a successful regular surveillance program ( 5 ). Therefore, in the treatment of HCC, recurrence after curative treatment is an important indicator that is negatively related to long-term survival ( 6 ). To improve recurrence-free survival (RFS) in patients with HCC, several studies on adjuvant therapy have been conducted; however, none of these studies provide sufficient evidence of improvement except for antiviral treatment for HBV- or HCV-related HCC ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…For decades, researchers have been exploring more sensitive biomarkers and developing more effective therapeutic strategies for HCC patients with a high risk of tumor recurrence. However, a great number of patients with HBV-HCC still suffer tumor recurrence [181,182]. Our woodchuck HCC study demonstrated that MTA1dE4, a major spliced variant of MTA1, may represent a more sensitive marker than total MTA1 in WHV-induced HCC [32].…”
Section: Translational Researches Based On the Woodchuck Modelmentioning
confidence: 85%
“…Moreover, LR is the mainstay of curative treatment and health-giving treatment for HCC, and the long-term survival of patients still remains undesirable since recurrence happens in about 54% of patients who underwent resection [ 38 , 39 ]. Recurrence after LR is highly associated with aggressive tumor characteristics, size of the tumor, presence of cirrhosis, Child–Pugh classification, alcohol consumption, and smoking [ 40 ].On the other hand, all HCC patients are not suitable for LR [ 41 ]. Ascites and uncorrectable coagulopathy are two major factors that reduce the number of candidates for surgery; furthermore, radiofrequency ablation has been suggested by the researcher as an alternative therapy for these CPT A and B HCC patients, and 3-year survival of patients reached up to 65% after it [ 42 ].…”
Section: Discussionmentioning
confidence: 99%